2022
DOI: 10.1007/s11920-022-01369-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin in the Management of Sleep and Circadian Disorders in the Context of Psychiatric Illness

Abstract: Purpose of Review We present a review of research on the role of melatonin in the management of sleep and circadian disorders, stressing current overall view of the knowledge across psychiatric disorders. Recent Findings Dysregulation of sleep and circadian rhythms has been established in several psychiatric and neurocognitive disorders for long. Recent research confirms this finding consistently across disorders. The secretion of melatonin in schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 102 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…Ironically, the reported prevalence of hypnotic agent and/or sedative use in this study mirrored findings from the first study of this kind, which was conducted 12 years ago among medical students in the Riyadh region, SA [ 33 ]. This continued pattern could be attributed to the availability and tolerability of exogenous melatonin, which replaced demand for other sleep aid agents [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ironically, the reported prevalence of hypnotic agent and/or sedative use in this study mirrored findings from the first study of this kind, which was conducted 12 years ago among medical students in the Riyadh region, SA [ 33 ]. This continued pattern could be attributed to the availability and tolerability of exogenous melatonin, which replaced demand for other sleep aid agents [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence indicates the safety and effectiveness of exogenous melatonin as a pharmacological supplement in regulating the circadian rhythm of the sleep–wake cycle in adults and children older than 11 years [ 13 , 14 , 15 ]. Moreover, melatonin showed positive impacts on sleep quality for other common forms of sleep disorders, such as insomnia, breathing-related sleep disorders, and sleep-related movement disorders [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we encourage future studies to examine how currently used antipsychotics for treating psychosis might influence the PG volume and MLT in parallel to changes in sleep parameters, and also consider the use of melatonin as potential treatment avenues for reducing side effects of antipsychotics [86][87][88], ameliorating various cognitive and information processing disturbances typically present in people with schizophrenia [89,90], and treating sleep disturbances in a range of psychiatric disorders, including but not limited to psychosis and mood disorder [91,92].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary melatonin has been investigated as a potential adjunctive treatment for schizophrenia, showing promise in improving sleep parameters, and counteracting metabolic adverse reactions and tardive dyskinesia symptoms caused by antipsychotic drugs (Duan, Jenkins, & Castle, 2021). Furthermore, melatonin is advantageous due to its low cost, minimal side effects, lack of drug interactions, and easy availability (Moon, Kim, Partonen, & Linnaranta, 2022). Imaging studies have revealed that patients with schizophrenia exhibit more severe pineal gland calcification and smaller parenchymal volume, suggesting a potential link between pineal gland calcification and the regulation of schizophrenia by melatonin (Takahashi et al, 2021).…”
Section: Schizophreniamentioning
confidence: 99%